Physical Activity Routine By Physical Activities Related To Body Mass Index - Hendra Rustiawan; Andang Rohendi; Syifa Nurbait; Siskha Noor Komala; Isna Daniyati Nursasih (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2020)
This study aims to find out relations of college student habbit on the physical education in sport activity with his body mass index. Physical activity are usually done by everyone, as well as college student at physical education. It is familiar. This study was conducted at a time, in 36 students who were all male sex with the age range of 20-24 years old. To known the result from the data will be processed, researchers used an instrument of the questionnaire. The questionnaire was immediately filled by each respondent without given any treatment previously. Category was obtained from the measurement of body mass index between height and weight each respondent. There is only one group in this research, no groups were compared. The method used is quantitative and data analysis using the technique chi square.  The data obtained were then processed with SPSS 21 series. After data processed, the results show there is a significant correlation between both variables.